Β2-adrenergic receptor signaling promotes pancreatic ductal adenocarcinoma (PDAC) progression through facilitating PCBP2-dependent c-myc expression. Issue 1 (1st April 2016) - Wan, Chunhua; Gong, Chen; Zhang, Haifeng; Hua, Lu; Li, Xiaohong; Chen, Xudong; Chen, Yinji; Ding, Xiaoling; He, Song; Cao, Wei; Wang, Yingying; Fan, Shaoqing; et al.
Highlights: Activated β2-AR interacts with PCBP2 in pancreatic cancer cells. β2-AR promotes c-myc expression in PDAC cells in a PCBP2-dependent manner. β2-AR and PCBP2 are upregulated in human pancreatic cancer tissues. High levels of β2-AR/PCBP2 predict poor prognosis in pancreatic cancer patients. Abstract: The β2-adrenergic receptor (β2-AR) plays a crucial role in pancreatic ductal adenocarcinoma (PDAC) progression. In this report, we identified poly(rC)-binding protein 2 (PCBP2) as a novel binding partner for β2-AR using immunoprecipitation-mass spectrometry (IP-MS) approach. The association between β2-AR and PCBP2 was verified using reciprocal immunoprecipitation. Importantly, we found significant interaction and co-localization of the two proteins in the presence of β2-AR agonist in Panc-1 and Bxpc3 PDAC cells. β2-AR-induced recruitment of PCBP2 led to augmented protein level of c-myc in PDAC cells, likely as a result of enhanced internal ribosome entry segment (IRES)-mediated translation of c-myc. The activation of β2-AR accelerated cell proliferation and colony formation, while knockdown of PCBP2 or c-myc restrained the effect. Furthermore, overexpression of PCBP2 was observed in human PDAC cell lines and tissue specimens compared to the normal pancreatic ductal epithelial cells and the non-cancerous tissues respectively. Overexpression of β2-AR and PCBP2 was associated with advanced tumor stage and significantly worsened prognosis in patients with PDAC. Our results elucidate a new molecular mechanism by which β2-AR signaling facilitates PDAC progression through triggering PCBP2-dependent c-myc expression.